2010
DOI: 10.1111/j.1471-0528.2010.02503.x
|View full text |Cite|
|
Sign up to set email alerts
|

Vaginoscopic approach to outpatient hysteroscopy: a systematic review of the effect on pain

Abstract: Background Vaginoscopy, also known as the 'no-touch' technique, is an alternative method for performing hysteroscopy without the need for a vaginal speculum to view the cervix or cervical instrumentation to grasp and steady the cervix.Objective To examine the effect of a vaginoscopic approach to outpatient hysteroscopy on the patients' experience of pain, compared with a traditional approach using a vaginal speculum.Search strategy MEDLINE, EMBASE, CINAHL and the Cochrane Library were searched for relevant art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…Performing hysteroscopy without a speculum or tenaculum (vaginoscopy technique) causes less pain than traditional hysteroscopy. 2,73 One trial randomized 126 women to vaginoscopy without anesthesia and the traditional approach with speculum, tenaculum, and 10 mL 3% mepivacaine intracervical block. 74 The hysteroscopy was performed with normal saline and a rigid 3.7-mm hysteroscope.…”
Section: Hysteroscopymentioning
confidence: 99%
“…Performing hysteroscopy without a speculum or tenaculum (vaginoscopy technique) causes less pain than traditional hysteroscopy. 2,73 One trial randomized 126 women to vaginoscopy without anesthesia and the traditional approach with speculum, tenaculum, and 10 mL 3% mepivacaine intracervical block. 74 The hysteroscopy was performed with normal saline and a rigid 3.7-mm hysteroscope.…”
Section: Hysteroscopymentioning
confidence: 99%
“…Literature shows that the best method of pain control for women undergoing traditional hysteroscopy is local anesthesia [30, 31]. However, a recent systematic review reported less pain during hysteroscopy in case of vaginoscopic approach (no anesthesia) compared with traditional hysteroscopic techniques, even with use of local anesthesia [32]. We showed a significant increase in the number of gynecologists using no anesthesia in 2009 compared with 2003.…”
Section: Discussionmentioning
confidence: 77%
“…A technique known as vaginoscopy, which involves the insertion of a hysteroscope into the uterine cavity without the use of a speculum or a genital tract instrumentation, can help histological sampling when access is limited, for example, in cases of vaginal stenosis [35].…”
Section: Endometrial Pathologymentioning
confidence: 99%